MANAJEMEN PENDAFTARAN CALON WALIKOTA DAN WAKIL WALIKOTA KOTA MANADO PADA PEMILIHAN WALIKOTA DAN WAKIL WALIKOTA MANADO TAHUN 2015 - DAMEK, ANDRIA; MAMENTU, MICHAEL; REMBANG, MAX (JURNAL ADMINISTRASI PUBLIK, 2018)
Indonesia's ability to organize elections is acknowledged by democratic countries in the world, butthere are various problems in the implementation of elections, proving that many things still need to beaddressed in relation to the elections themselves, such as election regulation, skill and mentality of theorganizers, , the ability and readiness of the institutions or supporting institutions, as well as the intelligenceand mentality of voter participants in the election of Regional Head itself. Election problems also occur in thein the Manado city elections of 2015, namely the issue at the registration stage of Mayor and Deputy MayorCandidates. This research aims to find the cause of the occurrence of consistency in determining Mayor andDeputy Mayor of Manado Year 2015 and get new formula about registration management of candidate ofRegion Head. This research uses qualitative research method. focused on registration management ofcandidates for Regional Head candidates. The results of this study were obtained from five aspects unearthedin the research: independence, impartiality, integrity, transparency and professionalism, it was found that therewere problems with each of these aspects. In the first four aspects the source of the problem is individual. The2cause is the weakness of the individual mentality in question. Mental uncertainty to face pressure and"temptation" results in poor registration in the Manado city elections of 2015. However, the main cause of thisproblem is the unprofessional nature of the election organizers themselves. The cause is the first in theimperfection of the policy made, the second is in the absence of adequate provision for the election practitioners,the matter of treatment for ex-convicted, and the third is not open (transparency) institutions related to this. itis still difficult to find the cause of this happening (why transparency is weak), but very strong tendency of"political power" that affect this process.Keywords: Management, Candidate Registration, Selection Of Regional Head